Sustainable Entrepreneurship Strategies for Salt Entrepreneurs in New Normal Business Concept - Issa Dyah Utami; Trisita Novianti (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Salt is one of the basic needs of Indonesian society. The salt production areas in Indonesia reach 37.4 thousand hectares, but the potential areas are merely around 53.2%. People's salt production has only been able to meet the need for households' daily consumption, while the industrial need is met from imports. The people's salt production needs to be increased to maintain the sustainability of salt farmers' business. Salt farmers require training about the strategies to improve the quality of salt production, manage finished products, and run the salt business independently. Studies on the analysis of the sustainability of people's salt business, particularly in terms of entrepreneurship aspect, are limited. Therefore, this present study analyzes the sustainability of people's salt business entrepreneurship with three triple bottom line criteria: people, planet, and profit. This study aims to formulate the framework of business strategies suitable for the condition of the salt business. The framework is constructed from the factors synthesized from the literature on previous studies. The results of this study are expected to be implemented by the government and business actors in making a decision and setting policies to determine the strategies for maintaining SMEs' salt business sustainability. This study applied the Analytical Network Process (ANP) method to determine the rating of the factors contributing to the continuity of the SMEs' salt business. The factors underlying sustainable entrepreneurship were identified from the literature studies based on the triple bottom line concept adapted to the conditions in Madura. The criteria of people include collaborative development, risk seizing, and innovative thinking, while the requirements of the planet cover eco-friendly packaging and waste controlling. Profit was seen from the aspects of government policy and unsettled finance. Then, the TOPSIS analysis was applied to analyze strategies based on the highest performance score. The results of data analysis show that government policy has the highest score as an alternative, and implementation of an e-supply chain is the strategy with the highest-ranking performance score.